Administrasi Keuangan,Sarana Dan Prasarana Di MIS Al-Musthafawiyah Medan - Mursal Aziz; Nur Hasana Ramadhani; Latifa Siregar; Rini Anggraini (Politeknik Kampar, 2024)
Financial administration is all activities, from setting up to managing everything, which are carried out to achieve common goals. Administration cannot be done by one person alone, because it requires cooperation between two or more people. In organizing educational facilities and infrastructure at MIS Al-Musthafawiyah, it is carried out through school budget planning and utilization of the school budget. The motive for this research is to find out the role of financial administration, facilities and infrastructure at MIS Al-Musthafawiyah Medan. The results of the research are financial administration, facilities and infrastructure. It is very important in the learning process to have adequate and efficient financial administration, facilities and infrastructure, so students will be more effective in learning.